INCREMENTAL INFORMATION CONTENT DALAM OPINI AUDIT UNQUALIFIED DENGAN PARAGRAF PENJELASAN - Leo, Lianny (Jurnal Akuntansi dan Keuangan Indonesia, 2007)
This study investigates whether there is any different market reaction to unqualified and unqualified with explanatory paragraph audit opinion. The result of empirical univariate and regression test on 291 firm-years, with balanced proportion between the two opinions, shows that there is a significant difference of stock returns between the two audit opinions around opinion announcement. Market appreciates the existence of explanatory paragraph in the unqualified audit opinion with higher excess returns compared to standard unqualified audit opinion. Overall this study shows incremental information content in unqualified with explanatory paragraph audit opinion.